Konsep Pengembangan Instrumen Penilaian Afektif Pada Mata Pelajaran Pendidikan Agama Islam Di SD Islam Nusantara - Halwa Anjumi; Moh. Muslih; Titien Soewastiningsih Soebari (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
This research aims to determine the concept of developing affective assessment instruments in Islamic Religious Education subjects at SD Islam Nusantara, Pekalongan City. Using qualitative research with a literature study approach. Data collection uses documentation techniques, namely by analyzing information regarding the concept of developing affective assessment instruments in Islamic Religious Education subjects. Then the information is analyzed with data obtained from relevant literature sources such as books and journals. The data analysis technique goes through several stages, namely preliminary analysis, data reduction, presenting data and drawing conclusions. The results of this research show that developing an affective assessment instrument in Islamic Religious Education subjects goes through the following steps: determining instrument specifications, writing the instrument, determining the instrument scale, determining the scoring system, reviewing the instrument, assembling the instrument, conducting trials, analyzing the instrument, carrying out measurements, interpret measurement results.